Modified Delphi survey for the evidence summarisation of patient decision aids: Study protocol - Durand, Marie-Anne (BMJ Open, 2019)
INTRODUCTION: Information included in a patient decision aid (PDA) can significantly influence patients’ decisions and is, therefore, expected to be evidence-based and rigorously selected and summarised. PDA developers have not yet agreed on a standardised process for the selection and summarisation of the supporting evidence. We intend to generate consensus on a process (and related steps and criteria) for selecting and summarising evidence for PDAs using a modified Delphi survey. METHODS AND ANALYSIS: We will develop an evidence summarisation process specific to PDA development by using a consensus-based Delphi approach, surveying international experts and stakeholders with two to three rounds. To increase generalisability and acceptability, we will distribute the survey to the following stakeholder groups: PDA developers, researchers with expertise in shared decision making, PDA development and evidence summarisation, members of the International Patient Decision Aids Standards (IPDAS) collaboration, policy makers with expertise in PDA certification and patient stakeholder groups. For each criterion, if at least 80% of survey participants rank the criterion as most important/least important, we will consider that consensus has been achieved. ETHICS AND DISSEMINATION: It is critical for PDAs to have accurate and trustworthy evidence-based information about the risks and benefits of health treatments and tests, as these decision aids help patients make important choices. We want to generate consensus on an approach for selecting and summarising the evidence included in PDAs, which can be widely implemented by PDA developers. Dartmouth College’s Committee for the Protection of Human Subjects approved this protocol. We will publish our results in a peer reviewed journal.